2022
DOI: 10.1177/1934578x221139082
|View full text |Cite
|
Sign up to set email alerts
|

Review of Herbal Medicines for the Treatment of Depression

Abstract: Depression, a mental illness that is receiving increasing attention, is caused by multiple factors and genes and adversely affects social life and health. Several hypotheses have been proposed to clarify the pathogenesis of depression, and various synthetic antidepressants have been introduced to treat patients with depression. However, these drugs are effective only in a proportion of patients and fail to achieve complete remission. Recently, herbal medicines have received much attention as alternative treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 186 publications
1
8
0
Order By: Relevance
“…It is sometimes referred to as an adaptogen plant or golden root. 3,9 It has been utilized as a physical and mental enhancer in traditional medicine. Using behavioral tests on rats, Mattioli et al demonstrated the antidepressant efficacy of Rhodiola rosea extract (10-20 mg/kg, PO for 3 weeks).…”
Section: Medical Herbs Useful For Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is sometimes referred to as an adaptogen plant or golden root. 3,9 It has been utilized as a physical and mental enhancer in traditional medicine. Using behavioral tests on rats, Mattioli et al demonstrated the antidepressant efficacy of Rhodiola rosea extract (10-20 mg/kg, PO for 3 weeks).…”
Section: Medical Herbs Useful For Depressionmentioning
confidence: 99%
“…3 In the depression-like behavior paradigm, the psychopharmacological mechanisms of RL were mostly associated with inhibition of monoamine oxidase A, modification of 5-HT content, and increased neuronal quantity and proliferation in depressed rats and mice. 9 . A notable recovery was shown in the Rhodiola roseatreated group compared with the placebo group in a phase III clinical trial that was randomized, double-blind, placebocontrolled, and used Rhodiola rosea extract (340-680 mg/day) for mild to moderate depression.…”
Section: Medical Herbs Useful For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Patients with depressive disorders have a higher probability of taking herbal medicines than other patients. 17 In Korea, the herbal medicines commonly prescribed for depressive disorders include Gami-soyosan, Banhasasim-tang, Ojeok-san, and Bojungikgi-tang. Given the Korean medical system, there is a high probability of co-administration of SSRIs and herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics show that depression remains a major burden in society, affecting approximately 280 million people worldwide [2]. Several pathological mechanisms of depression have been documented, including alterations in neurotransmitter systems, hypothalamus-pituitary-adrenal (HPA) axis activity, neuroinflammation, and changes in brain structures [3]. Norepinephrine and dopamine are neurotransmitters that play a role in reward processing and motivation, and their abnormal serum levels have been reported in depressed rodents [4].…”
Section: Introductionmentioning
confidence: 99%